HEPATITIS C VIRUS ANTIBODY PREVALENCE IN CHRONIC LIVER DISEASES AND SOME RISK GROUPS - M. Enver DOLAR,; Yaşar ACAR,; Bahri ATEŞ,; M. Emin CANER,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2020)
-